Piecemeal Transparency: An Appraisal of Regulation (EU) No. 2019/1381 on the Transparency and Sustainability of the EU Risk Assessment in the Food Chain. (18th September 2021) - NÍ CHEARNAIGH, Blánaid
Abstract : For some time, pressure was placed on the European Food Safety Authority concerning the manner in which it conducted risk assessments in relation to food safety. This pressure culminated in the introduction of Regulation (EU) No. 2019/1381 as the upshot to the European Citizens' Initiative on glyphosate. Concerns were expressed in the initiative regarding the transparency of the scientific studies used to evaluate pesticides, and following a Fitness Check conducted by the European Commission. Effectively, the new Regulation seeks to impose an obligation on EFSA to publish industry studies at the beginning of the risk assessment process. However, the mandatory nature of this obligation raises a number of concerns as to whether the urge to increase the transparency of the work of the EU authorities is more important than keeping the research confidential, two converse ideals in the realm of European law and effective processes. The present article submits that this codified focus on the risk assessment process and its accessibility for European citizens is a new frontier for transparency within the EU risk assessment processes. Yet while the changes pioneered by this framework are laudable, the Regulation is not without its qualifications.